Growth performance, carcass characteristics, fresh belly quality, and commercial bacon slicing yields of growing-finishing pigs from sire lines intended for different industry applications. (August 2019) - Lowell, J.E.; Schunke, E.D.; Harsh, B.N.; Bryan, E.E.; Stahl, C.A.; Dilger, A.C.; Boler, D.D.
Abstract: The objective was to control intrinsic and extrinsic factors associated with the production and slaughter of pigs to determine effects of sire line (Pietrain vs. Duroc ancestry) on growth performance, carcass and belly characteristics, and commercial bacon yields of growing-finishing pigs. There were no differences in growth performance ( P  ≥ 0.08) or belly processing characteristics ( P  ≥ 0.09). Pietrain sired pigs had a greater lean yield ( P  ≤ 0.01). Duroc sired pigs had darker, more highly marbled loins ( P  ≤ 0.04) and thicker bellies ( P  < 0.001). Bacon from Pietrain sired pigs had a greater ( P  = 0.04) lean to fat ratio with 1.58% increase ( P  = 0.04) in average bacon slice lean. Barrows had more highly marbled loins ( P  ≤ 0.01) and thicker bellies ( P  < 0.001) than gilts. Bacon from barrows had a greater slice area ( P  < 0.001) while bacon from gilts had a greater lean to fat ratio ( P  = 0.04).